Stagnant Wages, Sectoral Misallocation and Slowing Productivity Growth - Michaela Schmöller (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
I propose a two-sector endogenous growth model with heterogeneous sectoral productivity and nonlinear hiring costs to analyse the link between sectoral resource allocation, low productivity growth and stagnant real wages. My results suggest that an upward shift in employment, triggered for instance by a labor market reform, is beneficial in the long-run as it raises growth of technology, labor productivity and real wages. I show, however, that a slowdown in productivity and stagnation of real wages can in this setting constitute two sides of the same coin as a result of the shift in employment: In the immediate phase following the shock, labor productivity and real wages stagnate as employment gains are initially disproportionally allocated to the low productivity sector which limits the capacity for technology growth and depresses real wages and productivity. I show that due to the learning-by-doing growth externality in the high productivity sector the competitive equilibrium is not efficient as firms fail to internalize the effect of their individual labor allocation on aggregate growth. Subsidies to high productivity sector production constitute apt policy tools to alleviate welfare losses along the transition path.
Keywords: E20; E24; E60; O40; O41; 330; Subdued Wage Growth; Productivity Slowdown; Misallocation; Endogenous Productivity Dynamics; Labor Market Policies